ARPES on high-temperature superconductors: simplicity vs. complexity - Kordyuk, A.A.; Borisenko, S.V. (Физика низких температур, 2006)
A notable role in understanding of microscopic electronic properties of high temperature superconductors
(HTSC) belongs to angle resolved photoemission spectroscopy (ARPES). This technique
supplies a direct window into the reciprocal space of solids: the momentum–energy space
where quasiparticles (electrons dressed in clouds of interactions) dwell. Any interaction in the
electronic system, e.g., superconducting pairing, leads to modification of the quasiparticle spectrum—to
redistribution of the spectral weight over the momentum–energy space probed by
ARPES. Continued development of the technique had the effect that the picture seen through the
ARPES window became clearer and sharper until the complexity of the electronic band structure
of the cuprates had been resolved. Now, in the doping range optimal for superconductivity, the
cuprates much resemble a normal metal with well-predicted electronic structure, though with
rather strong electron–electron interaction. This principal disentanglement of the complex physics
from complex structure reduced the mystery of HTSC to the tangible problem of the interaction responsible
for quasiparticle formation. Here we present a short overview of resent ARPES results,
which, we believe, suggest a way to resolve the HTSC puzzle.